Analisis Penerapan Sistem Informasi Akuntansi pada UMKM Berbasis SAK EMKM dalam Mendukung Efektivitas dan Efisiensi Operasional - Rina Fitriani Fitriani; Aswin Dewanto Hadisumarto; Satria Satria; Ishak Husin; Marhakim Marhakim (Jurnal Sistem Informasi Akuntansi, 2026)
Digital transformation has shifted MSME operations toward online platforms, yet the integration of these activities into formal accounting systems remains a critical challenge. This study investigates the implementation of Accounting Information Systems (AIS) based on SAK EMKM standards within digital-based MSMEs to evaluate its impact on operational efficiency. Using a mixed-methods approach with a descriptive quantitative focus, data were gathered from 89 MSME owners under BPSDMP Kominfo Bandung through triangulation techniques, including surveys and interviews. The findings reveal that while over 95% of participants successfully utilize digital tools for marketing and payments, most have not integrated these transaction data into structured financial records. Current AIS implementation is predominantly limited to the operational phase rather than the accounting phase, resulting in financial reports that lack compliance with SAK EMKM. The study concludes that bridging the gap between digital adoption and standardized accounting is essential for enhancing business accountability. These results imply that MSMEs require specialized integration models to convert digital transaction data into reliable financial information for strategic decision-making in the competitive digital economy